Preparation method and application of Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material

By optimizing the carbon cloth pretreatment and stepwise electrodeposition process, the problems of Co3O4 nanowire structure stability and bimetallic hydroxide uniformity were solved, achieving efficient charge transport and reducing energy consumption, thereby improving the catalytic performance and stability of the electrode material.

CN121107466APending Publication Date: 2025-12-12ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511451736.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-11
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

In existing technologies, the Co3O4 nanowire structure has insufficient stability, the bimetallic hydroxide electrodeposition layer has poor uniformity, the interface charge transport efficiency is low, and the preparation process is energy-intensive and costly.

Method used

Carbon cloth was treated with piranha solution and then ultrasonically cleaned. A precursor solution with a molar ratio of Co2+:F-:urea of ​​1:2:2 was annealed under an Ar atmosphere to form a highly crystalline Co3O4 nanowire spherical array. Ni2+ and Fe3+, Co2+, Zn2+ or Cu2+ were then electrodeposited stepwise using a chronoamperometry method to form a uniform Fe, Co, Zn or Cu doped Ni(OH)2 layer.

Benefits of technology

It significantly improves the catalytic activity, structural stability and charge transport efficiency of composite electrode materials, reduces preparation energy consumption and simplifies the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121107466A_ABST
    Figure CN121107466A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material, and belongs to the technical field of electrocatalyst preparation. The preparation method comprises the following steps: pre-treating carbon cloth with a piranha solution, preparing a precursor solution from Co (NO3) 2.6 H2O, NH4F and Co (NH2) 2, preparing a Co3O4 nanowire by using a hydrothermal method in combination with an annealing process, preparing a bimetallic solution, and carrying out electro-deposition to obtain the Co3O4 nanowire coupled bimetallic hydroxide electrode material. A high-binding-force and high-crystallinity Co3O4 nanowire structure is constructed by pretreating carbon cloth, accurately controlling the molar ratio of Co < 2 + > to F <-> to urea in a precursor solution and combining a hydrothermal method with an annealing process, meanwhile, step-by-step electro-deposition is carried out in the range of-1.2 V to 0.2 V by adopting a chronoamperometry, each step stays for 5 seconds, and codeposition kinetics of Ni < 2 + > and Fe < 3 + >, Co < 2 + >, Zn < 2 + > or Cu < 2 + > is accurately controlled; through collaborative optimization of the means, the catalytic activity, the structural stability and the charge transfer efficiency of the composite electrode material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of preparation of electrocatalyst composite materials, and particularly relates to a preparation method and application of a Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material. BACKGROUND

[0002] At present, transition metal oxide (such as Co3O4) nanowires exhibit potential in the fields of electrocatalytic oxygen evolution reaction (OER), supercapacitors and the like due to their unique electronic structure and rich redox active sites. Carbon cloth (CC) as a conductive substrate can directly load Co3O4 nanowires through a hydrothermal method to form a three-dimensional porous structure to increase the specific surface area. In addition, the surface of Co3O4 can be modified by electrodeposition of bimetallic (such as nickel-iron, nickel-cobalt, nickel-copper, nickel-zinc and the like) hydroxides to further improve the OER catalytic activity of the material. In the prior art, there have been reports of preparing composite electrode materials by using a similar step-by-step method, but there are still the following key problems: ①The structural stability of Co3O4 nanowires is insufficient, and the crystallinity is poor, the surface defects are many, and the aggregation and shedding are easy due to improper precursor ratio or annealing conditions; ②The uniformity of the bimetallic hydroxide (such as nickel-iron, nickel-cobalt, nickel-copper, nickel-zinc and the like) electrodeposition layer is poor, and the active layer thickness is uneven and the Fe doping ratio is out of control due to traditional methods; ③The interface charge transfer efficiency of the composite material is low, and the interface resistance is increased due to lattice mismatch or interface oxide layer formation; ④The existing process has high energy consumption and cost, and needs multiple high-temperature treatments or uses noble metal catalyst templates, increasing the preparation period and process complexity. SUMMARY

[0003] To solve the above technical problems, the application provides a preparation method and application of a Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material. In view of the above problems, the application realizes performance breakthrough through the following key optimizations: 1. Pretreatment of carbon cloth: treatment with a piranha solution (H2SO4 : H2O2) combined with ultrasonic cleaning to enhance the hydrophilicity and functional group density of the carbon cloth surface and improve the nucleation uniformity of Co3O4 nanowires; 2. Direct generation of high-crystallinity Co3O4 nanowire spherical arrays by precursor solution ratio (Co 2+ : F - : urea = 1 : 2 : 2) and 450℃ annealing under Ar atmosphere, avoiding a secondary oxidation step; 3. Step-by-step electrodeposition strategy: step-by-step deposition in the range of -1.2 V ~ 0.2 V by using chronocoulometry to accurately control the deposition of Ni 2+ and Fe3+ Co 2+ Zn 2+ or Cu 2+ Co-deposition kinetics, forming uniform Fe, Co, Zn or Cu doped Ni(OH)2 layers, strengthening interface charge transport.

[0004] To achieve the above object, the technical scheme specifically adopted by the present application is as follows: A preparation method of a Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material, comprising the following steps: (1) Carbon cloth pretreatment: The carbon cloth is sequentially ultrasonically cleaned in acetone and ethanol for 10-40 min, then cleaned with deionized water for 3-5 times to remove residual ethanol, and finally ultrasonically cleaned in deionized water for 10-40 min; a solution of Ichthyophis monochrous is prepared to pretreat the carbon cloth; (2) Preparation of precursor solution: Co(NO3)2·6H2O, NH4F and Co(NH2)2 are added to deionized water, and magnetic stirring is performed for 30-60 min to obtain a uniform precursor solution; (3) Preparation of Co3O4 nanowire spherical array: The precursor solution is poured into a reaction kettle, and the pretreated carbon cloth is immersed in the precursor solution, and kept at 100-120℃ for 8-12 h; after cooling to room temperature, the carbon cloth and the precursor are repeatedly washed with deionized water, and dried in a vacuum oven at 40-80℃ for 2-10 h; the carbon cloth is placed in a tube furnace for annealing to obtain a Co3O4 nanowire spherical array; (4) Two kinds of metal salts are dissolved in deionized water and stirred for 30-50 min; (5) Electrodeposition: The carbon cloth is used as a working electrode, a platinum sheet is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode, and a chronopotentiometric electrodeposition is performed, then the carbon cloth is taken out, washed with deionized water for 3-5 times, and placed in a vacuum oven at 30-80℃ for drying for 2-8 h, to finally obtain a Co3O4 nanowire spherical array loaded bimetallic hydroxide composite material.

[0005] Further, the process of pretreating the carbon cloth with the Ichthyophis monochrous solution in step (1) is as follows: an Ichthyophis monochrous solution is prepared by mixing concentrated sulfuric acid and hydrogen peroxide at a volume ratio of 7:3, the washed carbon cloth is placed in the Ichthyophis monochrous solution, heated on a heating plate at 80-200℃ for 2-6 h; the Ichthyophis monochrous solution is poured out, ultrasonically cleaned with deionized water for multiple times until the deionized water is neutral, and then the carbon cloth is stored in deionized water for standby use.

[0006] Further, the concentration of the concentrated sulfuric acid is 98wt%, and the concentration of the hydrogen peroxide is 30wt%.

[0007] Further, in the step (2), the molar ratio of Co 2+ : F - : urea is 1 : 1-3 : 1-3, preferably 1 : 2 : 2.

[0008] Further, in the step (3), the annealing is performed at 400-500℃ for 2-4h in Ar atmosphere (100-200 sccm), preferably at 450℃ for 2h in 150 sccm Ar atmosphere.

[0009] Further, in the step (4), the two metal salts are one of iron salt, cobalt salt, zinc salt, copper salt, and nickel salt.

[0010] Further, in the step (4), the molar ratio of nickel to iron, cobalt, zinc or copper is 1-10 : 1, preferably 4 : 1.

[0011] Further, in the step (5), the electrodeposition is performed at -1.2 V ~ 0.2 V, and the electrodeposition is performed for 40-360 steps, with a residence time of 5 s for each step.

[0012] Further, the electrocatalyst prepared by the preparation method is used for electrolysis water oxygen evolution reaction.

[0013] As a preferred embodiment, a preparation method of a Co3O4 nanowire spherical array coupled nickel-iron hydroxide electrode material, comprising the following steps: (1) Carbon cloth pretreatment: The carbon cloth is sequentially ultrasonically cleaned in acetone and ethanol for 20 min, then cleaned with deionized water for 5 times to remove residual ethanol, and finally ultrasonically cleaned in deionized water for 20 min; Prepare the piranha solution for pretreatment of the carbon cloth: prepare the piranha solution according to a volume ratio of concentrated sulfuric acid to hydrogen peroxide of 7:3, put the washed carbon cloth into the piranha solution, heat on a 120℃ heating plate for 2h; pour off the piranha solution, ultrasonically clean with deionized water multiple times until the deionized water is neutral, then store the carbon cloth in deionized water for standby; (2) Preparation of precursor solution: Add Co(NO3)2·6H2O, NH4F, Co(NH2)2 into deionized water, magnetically stir for 30 min to obtain a uniform precursor solution, wherein the molar ratio of Co 2+ : F - : urea is 1 : 2 : 2; (3) Preparation of Co3O4 nanowire spherical array: The precursor solution is poured into a reaction kettle, and the pretreated carbon cloth is immersed in the precursor solution and kept at 100 DEG C for 10 hours; after cooling to room temperature, the carbon cloth and the precursor are repeatedly washed with deionized water and dried in a vacuum oven at 60 DEG C for 4 hours; the carbon cloth is placed in a tube furnace and annealed at 450 DEG C in an Ar atmosphere (150 sccm) for 2 hours, to obtain a Co3O4 nanowire spherical array; (4) Ni (NO3) 2.6H2O and Fe (NO3) 3.9H2O are dissolved in deionized water according to a molar ratio of nickel to iron of 4:1, and stirred for 30 minutes; (5) Electrodeposition: The carbon cloth is used as a working electrode, a platinum sheet is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode, and a timed potential electrodeposition is adopted, in a range of-1.2 V to 0.2 V, electrodeposition is performed for 200 steps, and each step stays for 5 seconds, then the carbon cloth is taken out, washed with deionized water for 5 times, and placed in a vacuum oven at 60 DEG C for drying for 4 hours, to finally obtain a Co3O4 nanowire loaded Fe-doped Ni (OH) 2 composite material.

[0014] Compared with the prior art, the catalytic activity, structural stability and charge transport efficiency of the composite electrode material are significantly improved through the synergistic optimization of the following technical means, and the specific advantages and technical effect correlation analysis is as follows: 1. Construction of Co3O4 nanowire spherical array structure with high bonding force and high crystallinity The carbon cloth is treated by a piranha solution (H2SO4 / H2O2) and supplemented with ultrasonic cleaning, and Co 2+ : F - : urea in the precursor solution is accurately controlled (1:2:2), and the annealing process is carried out at 450 DEG C in an Ar atmosphere.

[0015] The carbon cloth is treated by a piranha solution, rich oxygen-containing functional groups (such as -COOH and -OH) are introduced on the surface of the carbon cloth through strong oxidation, the nucleation site density of the nanowires is significantly increased, and the impurities on the surface of the carbon cloth are completely removed through ultrasonic cleaning, so that the Co3O4 nanowires grow uniformly and the bonding force with the substrate is improved (the peeling strength is increased by about 40% through testing), and the problem of easy falling off of the nanowires in the traditional method is solved.

[0016] F - As a morphology directing agent, it cooperates with urea to regulate the hydrothermal reaction kinetics and promote the directional growth of one-dimensional nanowires.

[0017] Ar atmosphere annealing avoids the oxidation of Co3O4 to form CoO, and the high temperature of 450 DEG C ensures that the precursor is completely converted into high crystallinity Co3O4, which is beneficial to the improvement of conductivity.

[0018] 2. Controllable deposition of uniform Fe, Co, Zn or Cu doped Ni(OH)2 layer The present application adopts chronoamperometry method for step-by-step electrodeposition in the range of -1.2 V ~ 0.2 V, with each step staying for 5 seconds, to accurately control the Ni 2+ co-deposition kinetics of Fe 3+ , Co 2+ , Zn 2+ or Cu 2+ .

[0019] The step-by-step potential switching balances the migration rate of Ni 2+ and Fe 3+ , Co 2+ , Zn 2+ or Cu 2+ by dynamically adjusting the electric field strength, avoiding the collapse of Ni(OH)2 layered structure caused by excessive Fe, Co, Zn or Cu.

[0020] 3. Significant improvement of heterojunction interface charge transport efficiency The present application directly grows Ni 0.8 Fe 0.2 (OH)2, Ni 0.8 Co 0.2 (OH)2, Ni 0.8 Zn 0.2 (OH)2 or Ni 0.8 Cu 0.2 (OH)2 layer on the surface of Co3O4 nanowire through hydrothermal-electrodeposition process matching design, avoiding the generation of interface oxide layer.

[0021] Ar atmosphere annealing inhibits the oxidation of Co3O4 surface, making it form a tight Co-O-Ni 0.8 Fe 0.2 (OH)2, Ni 0.8 Co 0.2 (OH)2, Ni 0.8 Zn 0.2 (OH)2 or Ni 0.8 Cu 0.2 (OH)2) layer chemical bonding interface.

[0022] Among them, Fe doping effect is the best, and the interface charge transfer resistance is reduced from 12 Ω·cm 2 of traditional process to 1.2 Ω·cm 2 . The nanowire structure provides a vertical electron transport channel for the Ni 0.8 Fe 0.2 (OH)2 layer, making the composite material in 10 mA / cm 2The OER overpotential at current density was reduced to 152 mV (compared to 290 mV in the conventional method), and the catalytic stability was improved to no significant decay after 100 h.

[0023] 4. Simplified process and cost advantages This invention provides a one-step hydrothermal synthesis method for Co3O4 nanowires, avoiding the secondary oxidation step of CoO→Co3O4 in traditional methods. Directly generating Co3O4 nanowires reduces the number of high-temperature treatments (from two to one). This not only saves energy but also reduces the thermal damage rate of the carbon cloth substrate. Attached Figure Description

[0024] Figure 1 SEM images of Example 1: (a) CC, (b) Co3O4 / CC, (c, d) Co3O4@Ni 0.8 Fe 0.2 (OH)2 / CC, (e)OER reaction followed by Co3O4@Ni 0.8 Fe 0.2 (OH)2 / CC, (f)Ni 0.8 Fe 0.2 (OH)2 / CC; Figure 2 The TEM image is from Example 1, (a) Co3O4@Ni 0.8 Fe 0.2 (b) Transmission electron microscopy (TEM) image of (OH)2 / CC, Co3O4@Ni 0.8 Fe 0.2 Lattice spacing of different crystal planes of (OH)2 / CC, FFT plots of (ce)S1, S2 and S3 squares; Figure 3 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 CV curves (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) (ad) and Cdl curves (e) for (OH)2 (M=Fe, Co, Cu and Zn). Figure 4 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 Performance data of oxygen evolution reaction in water electrolysis of (OH)₂ (M = Fe, Co, Cu, and Zn): a) Linear sweep voltammetry (LSV) curve, b) 10 mA·cm⁻¹ -2c) Overpotential and current density at 1.55 V operating voltage under the given conditions; d) Tafel slope plot; Figure 5 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 Oxygen evolution and Faraday efficiency of (OH)₂ (M = Fe, Co, Zn, and Cu); a) Ni 0.8 Fe 0.2 (OH)2, b) Ni 0.8 Co 0.2 (OH)2, c)Ni 0.8 Cu 0.2 (OH)2, d)Ni 0.8 Zn 0.2 (OH)2; Figure 6 The CV curves (ae) and Cdl plots (f) of different single metal samples electrodeposited in Examples 5-8 at different scan rates (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) in 1 M KOH are shown in Examples 5-8. Figure 7 Examples 5-8 show the OER performance of electrodeposited single metal samples at 1 M KOH: (a) LSV curves, (b) at 10 mA·cm⁻¹. -2 (c) Tafel slope, (d) EISNyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 8 Examples 5-8 illustrate the oxygen production and Faraday efficiency of electrodeposited single metal samples at 1 M KOH. Figure 9 XRD patterns of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13; Figure 10 The CV curves (ae) and Cdl plots (f) of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13 at different scan rates (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) in 1 M KOH are shown in Examples 9-13. Figure 11 For the OER performance of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13 at 1 M KOH, (a) LSV curve, (b) at 10 mA·cm -2(c) Tafel slope, (d) EIS Nyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 12 Examples 9-13 show the oxygen production and Faraday efficiency of Co3O4@Ni(OH)2 / CC electrodeposited at different times in 1 M KOH. Figure 13 Examples 14-17 show the CV curves (ae) and Cdl plots (f) of Co3O4@nickel-iron hydroxides with different NiFe ratios under 1 M KOH at different scan rates (10 mV / s, 20 mV / s, 30 mV / s, 40 mV / s, 50 mV / s, 60 mV / s). Figure 14 Examples 14-17 show the OER performance of Co3O4@nickel-iron hydroxides with different NiFe ratios at 1 M KOH: (a) LSV curves, (b) at 10 mA·cm⁻¹. -2 (c) Tafel slope, (d) EIS Nyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 15 Examples 14-17 show the oxygen production and Faraday efficiency of Co3O4@nickel-iron hydroxides with different NiFe ratios at 1 M KOH. Detailed Implementation

[0025] The technical solution and effects of the present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto. Example 1

[0026] This embodiment provides a method for preparing a Co3O4 nanowire spherical array-supported Fe-doped Ni(OH)2 composite electrode material, which specifically includes the following steps: (1) The carbon cloth was ultrasonically cleaned in acetone and ethanol for 20 min in sequence, then cleaned with deionized water 5 times to remove residual ethanol, and finally ultrasonically cleaned in deionized water for 20 min. (2) Prepare a piranha solution by mixing concentrated sulfuric acid (98wt%) and hydrogen peroxide (30wt%) in a volume ratio of 7:3. Place the carbon cloth washed in the first step into the piranha solution and heat it on a 120℃ heating plate for 2 hours. Pour off the piranha solution and ultrasonically clean it several times with deionized water until the deionized water is neutral. Then store the carbon cloth in the deionized water. (3) 1.164 g Co(NO3)2·6H2O, 0.2963 g NH4F and 0.4805 g Co(NH2)2 were added to 40 mL of deionized water in sequence and magnetically stirred at 800 rmp for 30 min to obtain a homogeneous mixed solution. (4) Pour the mixed solution into a 100 mL reactor and immerse the pretreated carbon cloth in the solution and keep it at 100 °C for 10 h. After cooling to room temperature, wash the carbon cloth and precursor repeatedly with deionized water and dry them in a vacuum oven at 60 °C for 4 h. (5) The carbon cloth was placed in a tube furnace and annealed at 450°C for 2 h in an Ar atmosphere (150 sccm) to obtain a Co3O4 nanowire spherical array. (6) Dissolve 3.4895 g Ni(NO3)2·6H2O and 1.212 g Fe(NO3)3·9H2O in 50 mL of deionized water and stir at 800 rpm for 30 min; (7) Carbon cloth was used as the working electrode, platinum sheet as the counter electrode, and saturated calomel electrode as the reference electrode. Timing potential electrodeposition was used. In the range of -1.2 V to 0.2 V, 200 electrodeposition steps were performed, with a dwell time of 5 s for each step. After that, the carbon cloth was removed, rinsed with deionized water 5 times, and placed in a vacuum oven at 60℃ to dry for 4 h. Finally, a composite material of Fe-doped Ni(OH)2 loaded on a Co3O4 nanowire spherical array was obtained. Example 2

[0027] Same as in Example 1, except that, (6) Dissolve 3.4895 g Ni(NO3)2·6H2O and 0.8731 g Co(NO3)2·6H2O in 50 mL of deionized water and stir at 800 rpm for 30 min. Example 3

[0028] Same as in Example 1, except that, (6) Dissolve 3.4895 g Ni(NO3)2·6H2O and 0.7248 g Cu(NO3)2·3H2O in 50 mL of deionized water and stir at 800 rpm for 30 min. Example 4

[0029] Same as in Example 1, except that, (6) Dissolve 3.4895 g Ni(NO3)2·6H2O and 0.8724 g Ni(NO3)2·6H2O in 50 mL of deionized water and stir at 800 rpm for 30 min.

[0030] Figure 1SEM images of Example 1: (a) CC, (b) Co3O4 / CC, (c, d) Co3O4@Ni 0.8 Fe 0.2 (OH)2 / CC, (e)OER reaction followed by Co3O4@Ni 0.8 Fe 0.2 (OH)2 / CC, (f)Ni 0.8 Fe 0.2 (OH)2 / CC; Figure 2 The TEM image is from Example 1, (a) Co3O4@Ni 0.8 Fe 0.2 (b) Transmission electron microscopy (TEM) image of (OH)2 / CC, Co3O4@Ni 0.8 Fe 0.2 Lattice spacing of different crystal planes of (OH)2 / CC, FFT plots of (ce)S1, S2 and S3 squares; Figure 3 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 CV curves (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) (ad) and Cdl curves (e) for (OH)2 (M=Fe, Co, Cu and Zn). Figure 4 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 Performance data of oxygen evolution reaction in water electrolysis of (OH)₂ (M = Fe, Co, Cu, and Zn): a) Linear sweep voltammetry (LSV) curve, b) 10 mA·cm⁻¹ -2 c) Overpotential and current density at 1.55 V operating voltage under the given conditions; d) Tafel slope plot; Figure 5 For the Fe, Co, Zn and Cu of Examples 1-4, Ni(OH)2 was doped respectively, and Co3O4@Ni was loaded on the surface of carbon cloth (CC). 0.8 M 0.2 Oxygen evolution and Faraday efficiency of (OH)₂ (M = Fe, Co, Zn, and Cu); a) Ni 0.8 Fe 0.2 (OH)2, b) Ni 0.8 Co 0.2 (OH)2, c)Ni 0.8 Cu0.2 (OH)2, d)Ni 0.8 Zn 0.2 (OH)2.

[0031] Depend on Figures 1-5 It can be seen that a spherical nanoflower structure of Co3O4 nanowire array is formed on the smooth surface of pure carbon cloth composed of carbon fibers. After electrodeposition, a layer of Ni is coated on the surface of the Co3O4 nanowires. 0.8 Fe 0.2 (OH)2 ensures the integrity of the Co3O4 nanowire array structure with its nanoflower-like structure, while forming a core-shell structure that remains stable after the OER reaction. Furthermore, transmission electron microscopy reveals that Co3O4@Ni 0.8 Fe 0.2 (OH)₂ / CC exhibits two regions: those with lattice fringes and those without. The lattice fringed regions and the corresponding FFT diffraction patterns correspond to the (220) and (111) crystal planes of Co₃O₄, respectively. The FFT diffraction patterns show an amorphous halo phenomenon, indicating that Ni… 0.8 Fe 0.2 (OH)₂ has an amorphous structure. In contrast, Co₃O₄@Ni is loaded on the surface of carbon cloth (CC). 0.8 M 0.2 OER performance testing of (OH)2 (M=Fe, Co, Zn and Cu) showed that Co3O4@Ni 0.8 Fe 0.2 (OH)2 / CC showed the highest Cdl (20.43 mF·cm). -2 ), at 10 mA·cm -2 The catalyst exhibits a minimum overpotential of 152 mV and a current density as high as 143.12 mA·cm⁻¹ at a potential of 1.55 V vs. RHE. -2 The lowest Tafel slope (34 mV·dec) -1 It exhibits the lowest AC impedance and 98% Faraday efficiency, demonstrating optimal OER activity.

[0032] Examples 5-8 Same as in Example 1, except that, (6) Take 4.3619 g Ni(NO3)2·6H2O, 6.06 g Fe(NO3)3·9H2O, 4.3655 g Co(NO3)2·6H2O, and 3.624 g Cu(NO3)2·3H2O respectively and dissolve them in 50 mL of deionized water. Stir at 800 rpm for 30 min.

[0033] Figure 6The CV curves (ae) and Cdl plots (f) of different single metal samples electrodeposited in Examples 5-8 at different scan rates (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) in 1 M KOH are shown in Examples 5-8. Figure 7 Examples 5-8 show the OER performance of electrodeposited single metal samples at 1 M KOH: (a) LSV curves, (b) at 10 mA·cm⁻¹. -2 (c) Tafel slope, (d) EISNyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 8 Examples 5-8 illustrate the oxygen production and Faraday efficiency of electrodeposited single metal samples at 1 M KOH. Depend on Figures 6-8 It can be seen that by electrodepositing different monometallic hydroxides M(OH) on the Co3O4 / CC surface... x (M = Fe, Ni, Co, Zn, and Cu), and performed an electrocatalytic water desorption oxygen reaction (OER). The results showed that Ni(OH)₂ had the highest Cdl (14.06 mF·cm⁻¹). -2 ), at 10 mA·cm -2 The catalyst exhibits a minimum overpotential of 178 mV and a current density as high as 165 mA·cm⁻¹ at a potential of 1.55 V vs. RHE. -2 The lowest Tafel slope (47 mV·dec) -1 It exhibits the lowest AC impedance and 96% Faraday efficiency, demonstrating optimal OER activity.

[0034] Examples 9-13 This embodiment is the same as Embodiment 1, except that: (6) Dissolve 4.3619 g of Ni(NO3)2·6H2O in 50 mL of deionized water and stir at 800 rpm for 30 min; (7) In this embodiment, pulse electrodeposition is used instead of chronopotential method to complete the deposition of Ni (OH)2 layer.

[0035] Set the parameters for pulse electrodeposition as follows: forward pulse voltage is -1.0 V, reverse pulse voltage is 0.5 V, pulse frequency is 10 Hz, duration of each pulse is 0.1 s, and total deposition time is 200 s-1800 s, specifically 200s, 600s, 1000s, 1400s, and 1800s.

[0036] This embodiment uses pulsed electrodeposition to replace chronopotential bonding to a certain extent, achieving controllable deposition of uniform iron-doped Ni(OH)2 layers, thus achieving basic technical effects while simplifying the process and reducing costs.

[0037] Figure 9 XRD patterns of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13; Figure 10 The CV curves (ae) and Cdl plots (f) of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13 at different scan rates (10mV / s, 20mV / s, 30mV / s, 40mV / s, 50mV / s, 60mV / s) in 1 M KOH are shown in Examples 9-13. Figure 11 For the OER performance of Co3O4@Ni(OH)2 / CC electrodeposited at different times in Examples 9-13 at 1 M KOH, (a) LSV curve, (b) at 10 mA·cm -2 (c) Tafel slope, (d) EIS Nyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 12 Examples 9-13 show the oxygen production and Faraday efficiency of Co3O4@Ni(OH)2 / CC electrodeposited at different times under 1 M KOH.

[0038] Depend on Figures 9-12 It can be seen that comparing different deposition times (t=200s, 600s, 1000s, 1400s, 1800s), the results show that different deposition times did not affect the crystal structure of the catalyst. Meanwhile, comparing the OER performance of these samples, when the total deposition time was 1000s, the obtained Co3O4@Ni... 0.8 Fe 0.2 (OH)₂ / CC exhibits the best OER activity, with the highest Cdl (14.06 mF·cm⁻¹). -2 ), at 10 mA·cm -2 The catalyst exhibits a minimum overpotential of 178 mV and a current density as high as 165 mA·cm⁻¹ at a potential of 1.55 V vs. RHE. -2 The lowest Tafel slope (47 mV·dec) -1 It boasts the lowest AC impedance and a Faraday efficiency of 96%.

[0039] Examples 14-17 This embodiment is the same as Embodiment 1, except that the molar ratios of Ni and Fe are 0.9:0.1, 0.7:0.3, 0.6:0.4, and 0.5:0.5, respectively. The other steps are the same.

[0040] Figure 13 Examples 14-17 show the CV curves (ae) and Cdl plots (f) of Co3O4@nickel-iron hydroxides with different NiFe ratios under 1 M KOH at different scan rates (10 mV / s, 20 mV / s, 30 mV / s, 40 mV / s, 50 mV / s, 60 mV / s). Figure 14 Examples 14-17 show the OER performance of Co3O4@nickel-iron hydroxides with different NiFe ratios at 1 M KOH: (a) LSV curves, (b) at 10 mA·cm⁻¹. -2 (c) Tafel slope, (d) EIS Nyquist plot; and the corresponding overpotential and current density at 1.55 V vs. RHE. Figure 15 Examples 14-17 show the oxygen production and Faraday efficiency of Co3O4@nickel-iron hydroxides with different NiFe ratios at 1 M KOH.

[0041] Depend on Figures 13-15 It can be seen that, comparing different Ni:Fe molar ratios (0.9:0.1, 0.8:0.2, 0.7:0.3, 0.6:0.4, 0.5:0.5), only when the Ni:Fe molar ratio is 0.8:0.2 does it show the highest Cdl (20.43 mF·cm). -2 ), at 10 mA·cm -2 The catalyst exhibits a minimum overpotential of 152 mV and a current density as high as 143.12 mA·cm⁻¹ at a potential of 1.55 V vs. RHE. -2 The lowest Tafel slope (34 mV·dec) -1 It exhibits the lowest AC impedance and 98% Faraday efficiency, demonstrating optimal OER activity.

[0042] Compared with the prior art, the key points and protection points of this invention are mainly reflected in the following specific technical means: 1. Optimization of carbon cloth pretreatment and nanowire growth process The carbon cloth was subjected to strong oxidation treatment using a piranha solution, combined with ultrasonic cleaning. The piranha solution introduced abundant oxygen-containing functional groups into the carbon cloth surface, significantly increasing the density of nanowire nucleation sites. At the same time, ultrasonic cleaning thoroughly removed surface impurities, ensuring uniform growth of Co3O4 nanowires and a significant improvement in their adhesion to the substrate.

[0043] 2. Improvement of the bimetallic hydroxide electrodeposition process A stepwise electrodeposition method using chronoamperometry was employed within the range of -1.2 V to 0.2 V, with each step pausing for 5 seconds to precisely control the Ni deposition. 2+ with Fe 3+ Co 2+ Zn 2+ or Cu 2+ Co-deposition kinetics were employed to achieve a Ni:Fe, Co, Cu, Zn molar ratio of 4:1. The electric field strength was dynamically adjusted through stepwise potential switching to balance the Ni content. 2+ with Fe 3+ Co 2+ Zn 2+ or Cu 2+ The migration rate is controlled to avoid excessive introduction of Fe, Co, Cu or Zn, ensuring the density and uniformity of the deposited layer, while improving the exposure rate of active sites.

[0044] 3. Optimized design of heterojunction interface Ni was directly grown on the surface of Co3O4 nanowires through a hydrothermal-electrodeposition process matching design. 0.8 Fe 0.2 (OH)2, Ni 0.8 Co 0.2 (OH)2, Ni 0.8 Zn 0.2 (OH)2 or Ni 0.8 Cu 0.2 (OH)2 layer, to avoid the formation of an interface oxide layer.

[0045] Ar atmosphere annealing inhibits the oxidation of Co3O4 surface, allowing it to react with Ni. 0.8 Fe 0.2 (OH)2, Ni 0.8 Co 0.2 (OH)2, Ni 0.8 Zn 0.2 (OH)2 or Ni 0.8 Cu 0.2 The (OH)2) layer forms a tight Co-O-Ni chemical bond interface, which significantly reduces the interfacial charge transfer resistance and improves charge transport efficiency.

[0046] Through the innovation of the above-mentioned technical means, this invention solves the problems of insufficient stability of Co3O4 nanowire structure, poor uniformity of bimetallic hydroxide electrodeposition layer and low charge transport efficiency of heterojunction interface in the prior art. It realizes the controllable deposition of Co3O4 nanowire structure with high bonding force and high crystallinity as well as uniform bimetallic hydroxide layer, which significantly improves the electrochemical performance and stability of composite material.

[0047] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a Co3O4 nanowire spherical array coupled bimetallic hydroxide electrode material, characterized in that, The preparation method includes the following steps: (1) Carbon cloth pretreatment: The carbon cloth was ultrasonically cleaned in acetone and ethanol for 10-40 min in sequence, then rinsed with deionized water 3-5 times to remove residual ethanol, and finally ultrasonically cleaned in deionized water for 10-40 min; a piranha solution was prepared to pretreat the carbon cloth. (2) Preparation of precursor solution: Add Co(NO3)2·6H2O, NH4F, and Co(NH2)2 to deionized water and stir magnetically for 30-60 min to obtain a homogeneous precursor solution. (3) Preparation of Co3O4 nanowires: The precursor solution was poured into a reaction vessel, and the pretreated carbon cloth was immersed in the precursor solution and kept at 100-120℃ for 8-12 h. After cooling to room temperature, the carbon cloth and precursor were repeatedly washed with deionized water and dried in a vacuum oven at 40-80℃ for 2-10 h. The carbon cloth was then placed in a tube furnace for annealing to obtain Co3O4 nanowires. (4) Dissolve the two metal salts in deionized water and stir for 30-50 min; (5) Electrodeposition: Carbon cloth was used as the working electrode, platinum sheet as the counter electrode, and saturated calomel electrode as the reference electrode. Timing potentiometric electrodeposition was used. Afterward, the carbon cloth was removed, rinsed with deionized water 3-5 times, and dried in a vacuum oven at 30-80℃ for 2-8 hours to finally obtain a Co3O4 nanowire-supported bimetallic hydroxide composite material.

2. The preparation method according to claim 1, characterized in that, The process of pretreating carbon cloth with piranha solution in step (1) is as follows: prepare piranha solution with a volume ratio of concentrated sulfuric acid to hydrogen peroxide of 7:3, put the washed carbon cloth into the piranha solution, and heat it on a heating plate at 80-200℃ for 2-6 hours; pour out the piranha solution, and ultrasonically clean it multiple times with deionized water until the deionized water is neutral. Then store the carbon cloth in deionized water for later use.

3. The preparation method according to claim 1, characterized in that, In step (2), Co in the precursor solution 2+ :F - The molar ratio of urea is 1:1-3:1-3.

4. The preparation method according to claim 3, characterized in that, In step (2), Co in the precursor solution 2+ :F - The molar ratio of urea is 1:2:

2.

5. The preparation method according to claim 1, characterized in that, In step (3), annealing is performed at 400-500℃ for 2-4 hours in an Ar atmosphere (100-200 sccm).

6. The preparation method according to claim 5, characterized in that, In step (3), the annealing is performed at 450°C for 2 h in an argon atmosphere of 150 sccm.

7. The preparation method according to claim 1, characterized in that, In step (4), the two metal salts are one of iron salt, cobalt salt, zinc salt, copper salt, and nickel salt.

8. The preparation method according to claim 7, characterized in that, In step (4), the molar ratio of nickel to iron, cobalt, zinc or copper is 1-10:

1.

9. The preparation method according to claim 1, characterized in that, In step (5), the electrodeposition is carried out in the range of -1.2 V to 0.2 V, in 40-360 steps, with a dwell time of 5 s for each step.

10. The preparation method according to claim 1, characterized in that, The electrocatalyst prepared by the method described above is used in the oxygen evolution reaction of water electrolysis.